Systemic priming and intranasal booster with a BcfA-adjuvanted acellular pertussis vaccine generates CD4+ IL-17+ nasal tissue resident T cells and reduces B. pertussis nasal colonization - Yount, Kacy S.; Hall, Jesse M.; Caution, Kyle; Shamseldin, Mohamed M.; Guo, Myra; Marion, Keirsten; Fullen, Audra R.; Huang, Yimin; Maynard, Jennifer A.; Quataert, Sally A.; Deora, Rajendar; Dubey, Purnima (Frontiers in Immunology, 2023)
Introduction Resurgence of pertussis, caused by Bordetella pertussis, necessitates novel vaccines and vaccination strategies to combat this disease. Alum-adjuvanted acellular pertussis vaccines (aPV) delivered intramuscularly reduce bacterial numbers in the lungs of immunized animals and humans, but do not reduce nasal colonization. Thus, aPV-immunized individuals are sources of community transmission. We showed previously that modification of a commercial aPV (Boostrix) by addition of the Th1/17 polarizing adjuvant Bordetella Colonization Factor A (BcfA) attenuated Th2 responses elicited by alum and accelerated clearance of B. pertussis from mouse lungs. Here we tested whether a heterologous immunization strategy with systemic priming and mucosal booster (prime-pull) would reduce nasal colonization. Methods Adult male and female mice were immunized intramuscularly (i.m.) with aPV or aPV/BcfA and boosted either i.m. or intranasally (i.n.) with the same formulation. Tissue-resident memory (TRM) responses in the respiratory tract were quantified by flow cytometry, and mucosal and systemic antibodies were quantified by ELISA. Immunized and naïve mice were challenged i.n. with Bordetella pertussis and bacterial load in the nose and lungs enumerated at days 1-14 post-challenge. Results We show that prime-pull immunization with Boostrix plus BcfA (aPV/BcfA) generated IFNγ+ and IL-17+ CD4+ lung resident memory T cells (TRM), and CD4+IL-17+ TRM in the nose. In contrast, aPV alone delivered by the same route generated IL-5+ CD4+ resident memory T cells in the lungs and nose. Importantly, nasal colonization was only reduced in mice immunized with aPV/BcfA by the prime-pull regimen. Conclusions These results suggest that TH17 polarized TRM generated by aPV/BcfA may reduce nasal colonization thereby preventing pertussis transmission and subsequent resurgence.